Potentiating Lung Mucosal Immunity Through Intranasal Vaccination - Nelson, Sean A.; Sant, Andrea J. (Frontiers in Immunology, 2021)
Yearly administration of influenza vaccines is our best available tool for controlling influenza virus spread. However, both practical and immunological factors sometimes result in sub-optimal vaccine efficacy. The call for improved or even universal influenza vaccines within the field has led to development of pre-clinical and clinical vaccine candidates that aim to address limitations of current influenza vaccine approaches. Here, we consider the route of immunization as a critical factor in eliciting tissue resident memory (Trm) populations that are not a target of current licensed intramuscular vaccines. Intranasal vaccination has the potential to boost tissue resident B and T cell populations that reside within specific niches of the upper and lower respiratory tract. Within these niches, Trm as poised to respond rapidly to pathogen re-encounter by nature of their anatomic localization and their ability to rapidly deliver anti-pathogen effector functions. Unique features of mucosal immunity in the upper and lower respiratory tracts suggest that local antigen is required for the elicitation of protective B and T cell immunity as these sites. We consider the important attributes of a rationally designed intranasal vaccine. Finally, we discuss outstanding questions and fields of future inquiry in the field of lung mucosal immunity.